Pretreatment with Astragalus polysaccharide alleviates heat stroke–induced intestinal injury in mice - Shan, Niqi; Wang, Linxiao; Duan, Chujun; Wu, Yilin; Jing, Yangmengjie; Fan, Hanyin; Wang, Shuai; Wang, Yuling; Wang, Shijia; Liu, Hui; Cheng, Kun; Liu, Lin; et al. (Frontiers in Pharmacology, 2025)
BackgroundHeat stroke (HS) is a life-threatening illness. For HS, prevention is more important than treatment. Astragalus polysaccharides (APS), a major active ingredient of Astragalus membranaceus (Fisch.) Bunge, has multiple bioactivities, including anti-inflammatory and immunoregulation. This study aimed to evaluate the protective effects of APS on intestinal injury caused by HS.MethodsMice were randomized to different groups. After 1 week of APS treatment, a mouse HS model was constructed and evaluated. Intestinal injury was assessed via histopathological examination, and the inflammation level was quantified via quantitative PCR. Flow cytometry and immunofluorescence analyses were used to detect neutrophil infiltration. Gut microbiota was analyzed via 16S rRNA sequencing. Moreover, network pharmacology was employed to analyze the potential targets and functional enrichment of APS. The apoptosis levels were detected in mouse intestinal tissues and IEC-6 intestinal epithelial cells.ResultsAPS pretreatment (50 mg/kg BW) prolonged the survival time, delayed the increasing rate of core temperature, and markedly improved organ injuries of HS mice. APS pretreatment improved the pathological changes in the intestine, inhibited inflammation, and reduced neutrophil infiltration. APS enhances the richness of intestinal flora and may shift microbiota functions, thereby benefiting vitamin B metabolism. Network pharmacology analysis indicated the apoptosis pathway as a potential target of APS. In vivo experiments using mouse HS model and in vitro experiments using IEC-6 cells confirmed the inhibitory effect of APS on apoptosis.ConclusionThe preventive effects of APS on HS-induced intestinal injury include the alteration of intestinal microbiota composition and anti-inflammatory and antiapoptotic capacity.